EFFECT OF SHIFT WORK SLEEP DISORDER SYMPTOMS ON ATTENTION FUNCTION: A CROSS-SECTIONAL STUDY AMONG FACTORY WORKERS IN JEPARA - Arinta Puspita Wati; Aditya Kurnianto; Retnaningsih Retnaningsih; Dwi Pudjonarko; Herlina Suryawati; Gita Fajar Wardhani (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2026)
Introduction: Attention plays a role in supporting productivity and safety in industrial environments, particularly among shift workers. Shift Work Sleep Disorder (SWSD), experienced by those on rotating or night shifts, is characterized by insomnia and/or excessive daytime sleepiness (EDS), both of which can decrease attentional function. These prevalence rates reaches up to 76.4% and 60.7% respectively, higher than in the general population. Attention impairment in shift workers has been linked to an increased risk of occupational accidents. Objective: To analyze the effect of SWSD symptoms on attention function among factory workers. Methods: A cross-sectional study was conducted in November 2024 involving 51 factory workers in Jepara. The Insomnia Severity Index, Epworth Sleepiness Scale, and Digit Span Test were employed to assess insomnia, EDS, and attention, respectively. Chi-square tests and logistic regression were used to analyze associations. Results: SWSD was found in 29.4% of participants and was significantly associated with attention impairment (RR = 2.4; 95% CI: 1.417–4.064; p = 0.002). Both insomnia (RR = 2.15; p = 0.016) and EDS (RR = 2.00; p = 0.019) increased the risk of impaired attention. Participants with both symptoms had the highest risk (RR = 2.17; p = 0.008). Multivariate analysis revealed that insomnia remained independently associated with impaired attention (AOR = 4.129; p = 0.018). Conclusion: EDS combined with insomnia increases the risk of attention impairment. Insomnia was found to be an independent predictor. These findings highlight the importance of sleep disorder screening to reduce the risk of attentional impairment and prevent occupational accidents in shift work.